2017
DOI: 10.1111/phn.12315
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Health through the Lens of Home Visitors, Supervisors, and Administrators: The Florida Maternal, Infant, and Early Childhood Home Visiting Program

Abstract: Home visitors in the Florida MIECHV program served as trusted confidants that helped families navigate social services. Future research should focus on the impact that home visiting has on immigrant health and whether this impact is maintained over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…The pathway of Restricted access to resources in our study was connected to education level, but it also included other groups such as those families who have recently arrived in the country, or those who may have high education but do not speak Swedish. Similar findings are presented in a study of home visiting families’ needs and challenges from the United States [ 37 ] where the focus was on immigrant populations, indicating that this pathway is of higher relevance in communities with higher levels of migrants. The authors found that language, social and physical isolation, economic hardship, citizenship status and mistrust of formal systems acted as barriers to access to healthcare and social services [ 37 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The pathway of Restricted access to resources in our study was connected to education level, but it also included other groups such as those families who have recently arrived in the country, or those who may have high education but do not speak Swedish. Similar findings are presented in a study of home visiting families’ needs and challenges from the United States [ 37 ] where the focus was on immigrant populations, indicating that this pathway is of higher relevance in communities with higher levels of migrants. The authors found that language, social and physical isolation, economic hardship, citizenship status and mistrust of formal systems acted as barriers to access to healthcare and social services [ 37 ].…”
Section: Discussionsupporting
confidence: 80%
“…Similar findings are presented in a study of home visiting families’ needs and challenges from the United States [ 37 ] where the focus was on immigrant populations, indicating that this pathway is of higher relevance in communities with higher levels of migrants. The authors found that language, social and physical isolation, economic hardship, citizenship status and mistrust of formal systems acted as barriers to access to healthcare and social services [ 37 ]. While the elements are very similar to the ones found in our study, the organization of the pathways differed.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the absence of interpreters, the patient is disadvantaged and cannot receive the correct information (Hadziabdic & Hjelm, ). The public health nurses should be culturally competent (Jean‐Baptiste et al., ; Riner, ) and focus on the health and well‐being of the child, regardless of their ethnic background. To promote the health of the child, good interaction with the parents is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Home‐visiting programs provide critical social support for families living in high‐risk situations, including mothers who are low‐income, young, pregnant for the first time, or are of ethnic minority or immigrant status, along with parents who are at higher risk of child maltreatment or lacking strong informal support networks (Avellar & Supplee, ; Jack, DiCenso, & Lohfeld, ; Jean‐Baptiste et al., ; Landy et al., ; Paris, ). These are among the risk factors that are identified through a statewide risk screen that is conducted in Florida for every pregnant woman and new mother to streamline referrals to home‐visiting programs (Hardt et al., ).…”
Section: Social Supportmentioning
confidence: 99%